Social Action Youth Church of Central Kalimantan through Churches, Educational institutions and Civil Societies - Wirawan, Aprianto; Maling, Akius; Malau, Reynhard; Ullo, Pence (CV. Media Digital Publikasi Indonesia, 2023)
The background of our research is based on the existence of stigmas in Christian society regarding the fact that present youth, other than being predicted as future leaders, are at the crossroads of searching for participation inside and outside the church. Thus, based on these phenomena, church youth tend to be labeled as critical but feeble community members when dealing with service realities in church and educational institutions. The qualitative research method applied interviews to unearth the research subjects' narratives as a tribute to the youth's silenced voices. The research aimed to show the intertwined journey—both at the beginning, intersection, and turning point of the journey itself—as a citizen of the church as well as a citizen of society who is responsible for their faith. Results of the project showed that church youth were not only involved in school participation but also in church service circles and social actions